Modern history of visual art in Southern Nigeria - Fourchard, Laurent (Africas: Languages, History and Arts, 2003)
This books takes into consideration the changes that have occurred within the visual art landscape in Nigeria during the 20th century. This historical change is the result of new cultural exchanges between Africa, Europe and America, exchanges that developed different artistic practices and promoted new patrons. In this framework, cities have played a fundamental role in the development of modern art, especially because of the presence of a local or international art market. All the chapters of this book are related to specific Southern Nigerian cities: some are places of ancient royal art patronage (bronze casting in Benin City), some are city market where various popular expression of art could have developed (calendar in Onitsha), a few are strictly university based (Nsukka) but most of them have welcome elements of artistic lineages scattered all over Nigeria (the Fákéye family for instance).